National and Pan-African citizens. The Ibadan “African Woman” conference of 1960 - (:unkn) unknown (My University, 2021)
In August 1960, the conference entitled “The African Woman Designs her Future” opened at the University of Ibadan, in south-western Nigeria. Fifty-five women from eight West African countries came together for the first time across linguistic and colonial lines to discuss the future of African women in independent nations and in a new Africa, free from colonial domination. The analyses proposed by the delegates show their willingness to redefine their gender roles by imagining new rights and duties that would enable them to build their positions as national and Pan-African citizens. However, this radiant moment was short-lived, and national political logics prevailed over Pan-African discourses. Nevertheless, these debates were to constitute a framework for national organizations and mobilizations in the years to come, and for West African feminist theoretical reflections in the decades that followed.
Keywords: African Research